A Preliminary Exposé of Systemic Functional Theory Fundamentals - Taofeek Olaiwola Dalamu (Universitas Cokroaminoto Palopo, 2017)
The study attempted to explain fundamentals of Systemic Functional Theory as textual analytical instruments. The basis was to demonstrate the applications of Ideational, Interpersonal and Textual Metafunctions as alternative semiotic resources that provide composite meaning potential to the structure of the clause. For illustration, six clauses in the advert of Premium Pension Limited were used as textual elements which the three metafunctions were applied. The study revealed conditionality, sensitizationality, judgmentality as well as integrity as the nuggets of the message. In addition, the ad tends to propound solutions to the financial security of the future of the people. The solution is for the recipients to negotiate and begin savings with Premium Pension Limited whose concern is how to care for the people in their old age. Above all, the study concluded that Halliday’s theory as a very practicable tool of textual analysis for researchers.